2022
DOI: 10.3390/life12081189
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Non-Alcoholic Fatty Liver Disease and Coronary Artery Disease: The Liver-Heart Axis

Abstract: Non-alcoholic fatty liver disease (NAFLD) represents the hepatic expression of the metabolic syndrome and is the most prevalent liver disease. NAFLD is associated with liver-related and extrahepatic morbi-mortality. Among extrahepatic complications, cardiovascular disease (CVD) is the primary cause of mortality in patients with NAFLD. The most frequent clinical expression of CVD is the coronary artery disease (CAD). Epidemiological data support a link between CAD and NAFLD, underlain by pathogenic factors, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 169 publications
0
14
0
Order By: Relevance
“…In aging how-ever, the cellular composition of the different WAT depots shifts to facilitate increased inflammatory cell infiltration [75]. The resultant release of proinflammatory cytokines TNF-α and IL-6 contributes to inflammaging [76] and, in concert with oxidative stress and lipotoxicity, leads to a higher prevalence of metabolic disease in the elderly and, inter alia, promotes NAFLD development [77,78,79]. In this context, we showed that the visceral WAT depot contributes to the pathogenesis of NAFLD by displayingwithin this depota combination of different and independently regulated cell death mechanisms (apoptosis, necrosis, necroptosis, and autophagy) as well as fibrosis [80].…”
Section: Adipocytes Of White Adipose Tissuementioning
confidence: 99%
“…In aging how-ever, the cellular composition of the different WAT depots shifts to facilitate increased inflammatory cell infiltration [75]. The resultant release of proinflammatory cytokines TNF-α and IL-6 contributes to inflammaging [76] and, in concert with oxidative stress and lipotoxicity, leads to a higher prevalence of metabolic disease in the elderly and, inter alia, promotes NAFLD development [77,78,79]. In this context, we showed that the visceral WAT depot contributes to the pathogenesis of NAFLD by displayingwithin this depota combination of different and independently regulated cell death mechanisms (apoptosis, necrosis, necroptosis, and autophagy) as well as fibrosis [80].…”
Section: Adipocytes Of White Adipose Tissuementioning
confidence: 99%
“…In addition, in subjects with NAFLD, inflammation appeared as increased levels of cytokines and chemokines in peripheral blood, such as IL-6, TNF-α, CRP, and MCP-1, which further accelerated atherosclerotic CVD by increasing plasminogen activator inhibitor-1 (PAI-1) and adhesion molecules levels in endothelial cells, reducing nitric oxide production, promoting the influx of low-density lipoprotein (LDL) into macrophages, and stimulating vascular smooth muscle cell proliferation ( 110 ). Besides, endothelial dysfunction and impaired endothelial flow-mediated vasodilatation observed in NAFLD patients could cause chronic inflammation, increased vasoconstriction, and augmented production of prothrombotic factors, resulting in an increased risk of atherosclerotic cardiovascular events ( 111 ). Furthermore, endothelial dysfunction was regarded as an independent risk factor for the occurrence and development of CHD ( 111 ).…”
Section: Metabolic Organ-secreted Factors Linking Nafld To Cvdmentioning
confidence: 99%
“…Besides, endothelial dysfunction and impaired endothelial flow-mediated vasodilatation observed in NAFLD patients could cause chronic inflammation, increased vasoconstriction, and augmented production of prothrombotic factors, resulting in an increased risk of atherosclerotic cardiovascular events ( 111 ). Furthermore, endothelial dysfunction was regarded as an independent risk factor for the occurrence and development of CHD ( 111 ). In short, lipid disturbances, IR, inflammation, and endothelial dysfunction are strongly associated with a higher risk of atherosclerotic CVD in NAFLD patients.…”
Section: Metabolic Organ-secreted Factors Linking Nafld To Cvdmentioning
confidence: 99%
“…Furthermore, it has a detrimental impact on cardiovascular health, including ischemic heart disease and stroke, which are more common causes of death in this population [ 4 , 5 , 6 , 7 ]. While the exact causal relationship between NAFLD and cardiovascular disease (CVD) remains unclear, growing evidence suggests that NAFLD is associated with an increased risk of CVD, independent of known CVD risk factors [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%